Who times the foreign exchange market? Corporate speculation and CEO characteristics - Beber, Alessandro; Fabbri, Daniela (Journal of Corporate Finance, 2012)
This paper shows that managers' personal beliefs and individual characteristics explain a large share of the substantial time-variation of derivative use beyond firm, industry, and market fundamentals. We construct a panel data set of foreign currency derivative holdings and currency exposures for U.S. non-financial firms. We use a novel approach to build a firm-specific foreign exchange return. We find that managers adjust derivatives notional amounts in response to past foreign exchange returns, as if they were forming views on future currency prices. We then construct an empirical measure of speculative behavior for each firm to investigate the profile of the speculator. Firms where the CEO holds an MBA degree, is younger, and has less previous working experience speculate more. These results are consistent with overconfident managers taking more risk.